Influence of distance from home to invasive centre on invasive treatment after acute coronary syndrome: a nationwide study of 24 910 patients. Issue 1 (4th November 2010) - Hvelplund, Anders; Galatius, Søren; Madsen, Mette; Rasmussen, Jeppe Nørgaard; Sørensen, Rikke; Fosbøl, Emil Loldrup; Madsen, Jan Kyst; Rasmussen, Søren; Jørgensen, Erik; Thuesen, Leif; Møller, Christian Holflod; Abildstrøm, Steen Zabell
Abstract : Objective: To investigate whether distance from a patient's home to the nearest invasive centre influenced the invasive treatment strategy in acute coronary syndrome (ACS). Methods: This was an observational cohort study using nationwide registries involving 24 910 patients admitted with ACS (median age 67, range 30–90 years). All persons were grouped in tertiles according to the distance from their residence to the invasive centre. Cox proportional hazard models were applied to estimate the differences in coronary angiography and revascularisation rate within 60 days of admission according to the distance to the centre. The end points were coronary angiography and subsequent revascularisation. Results: Of 24 910 patients with a first ACS, 33% resided <21 km from one of the five invasive centres in Denmark, 33% lived between 21 and 64 km away and 34% lived >64 km away. The incidence of coronary angiography was 68% for long distance versus 77% for short distance (p<0.05), with an HR of 0.78 (95% CI 0.75 to 0.81, p<0.0001). Adjustment for patient characteristics such as age, sex, co-morbidity and socioeconomic status did not attenuate the difference (HR 0.74, 95% CI 0.71 to 0.77, p<0.0001). Furthermore, revascularisation in the subgroup examined with coronary angiography was less likely for those residing a long distance from the invasive centre compared with those living nearer (adjusted HR of 0.82 (95% CI 0.78 to 0.85, p<0.0001). Conclusions: In patients hospitalised with ACS, invasive examination and treatment were less likely the further away from an invasive centre the patients resided, thus equal and uniform invasive examination and treatment was not found.